2009
DOI: 10.1038/oby.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Social Stress, Visceral Obesity, and Coronary Artery Atherosclerosis in Female Primates

Abstract: Our previous work in cynomolgus monkeys demonstrated significant relationships between (i) social reorganization stress and visceral fat deposition, and (ii) central fat deposition and coronary artery atherosclerosis (CAA). Nevertheless, direct relationships between CAA and visceral fat have not been demonstrated in people or animals, nor have relationships among stress, visceral obesity, and CAA been observed within a single study. Here, we examine the hypothesis that visceral obesity provides a link between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 37 publications
5
46
0
1
Order By: Relevance
“…This study was conducted in a large, middle-aged and elderly prospective population-based sample. We observed that participants who experienced stressful events at baseline had an increased risk of developing metabolic syndrome after 6.5 years, which is consistent with previous prospective studies (Bergmann et al, 2014;Lee et al, 2014;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002) and pre-clinical studies in primates (Jayo et al, 1993;Shively et al, 2009). We are however the first to investigate the existence of a graded relationship (Bergmann et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…This study was conducted in a large, middle-aged and elderly prospective population-based sample. We observed that participants who experienced stressful events at baseline had an increased risk of developing metabolic syndrome after 6.5 years, which is consistent with previous prospective studies (Bergmann et al, 2014;Lee et al, 2014;Raikkonen et al, 2007;Troxel et al, 2005;Vitaliano et al, 2002) and pre-clinical studies in primates (Jayo et al, 1993;Shively et al, 2009). We are however the first to investigate the existence of a graded relationship (Bergmann et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, it remains to be investigated if DOM mice might develop other stress-associated diseases despite being metabolically healthy. This conclusion is supported by accumulating evidences for a physiological 'cost of being dominant' in naturalistic and semi-naturalistic settings (Shively et al, 2009, Sapolsky 2005, Bartolomucci et al, 2005, Gesquiere et al, 2012.…”
Section: Dominant Mice Are Resilient To Stress-induced Mets and T2dsupporting
confidence: 59%
“…Most mammals live in societies, social hierarchies are widespread, and positive and negative social relationships as well as the socioeconomic status affect mood and parallel disease/well-being. In this scenario, dominance or high socioeconomic status are often associated with priority of access to resources and are considered protective for the development of a number of pathologies (Tamashiro et al, 2007, Shively et al, 2009, Sapolsky 2005, Bartolomucci et al, 2005, Gesquiere et al, 2012. This is particularly true under stable conditions or wealthy societies (Shively et al, 2009, Sapolsky 2005, Bartolomucci et al, 2005, Gesquiere et al, 2012.…”
Section: Dominant Mice Are Resilient To Stress-induced Mets and T2dmentioning
confidence: 96%
“…As in people, obesity is associated with type two diabetes in Old World monkeys (Wagner et al 2006;Chavez et al 2009). Central fat deposition patterns are associated with social stress as well as carotid and coronary artery atherosclerosis in cynomolgus monkeys and with cardiovascular disease in people (Shively et al 2009). Finally, Old World monkeys are optimal models for investigations involving cognitive decline and Alzheimer's disease due to their similarities to humans in central nervous system mobility (Gallagher and Rapp 1997;Voytko and Tinkler 2004;Kulstad et al 2005;Zeng et al 2006).…”
Section: Discussionmentioning
confidence: 99%